Ordinary girls : a memoir - Díaz, Jaquira (Algonquin Books of Chapel Hill, 2019)
"Jaquira Díaz writes an unflinching account of growing up as a queer biracial girl searching for home as her family splits apart and her mother struggles with mental illness and addiction. From her own struggles with depression and drug abuse to her experiences of violence to Puerto Rico's history of colonialism, every page vibrates with music and lyricism"--